2009
DOI: 10.1161/circulationaha.108.822205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuronal Nitric Oxide Synthase on Human Coronary Artery Diameter and Blood Flow In Vivo

Abstract: Background-Nitric oxide (NO)-mediated local regulation of vascular tone is considered to involve endothelial NO synthase (eNOS). However, we recently reported that human forearm basal microvascular tone in vivo is tonically regulated by neuronal NO synthase (nNOS), in contrast to an acetylcholine-stimulated reduction in tone, which is eNOS dependent. Here, we investigated the in vivo effects of an nNOS-selective inhibitor, S-methyl-L-thiocitrulline (SMTC), on the human coronary circulation and on flow-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
111
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 49 publications
(51 reference statements)
11
111
0
5
Order By: Relevance
“…PGI2 and Relative Contribution to Flow-Mediated Dilation Doshi et al 94) found that administration of NOS inhibitor N G -monomethyl-L-arginine (L-NMMA) completely abolished FMD of the brachial artery following 5 minutes of wrist cuff occlusion, with no difference in the hyperemic stimulus; however, L-NMMA does not completely block the FMD response when the occlusion cuff is placed on the upper arm 94,95) (see Table 1). Similarly, L-NMMA does not completely abolish FMD in the radial 11,27,28,[96][97][98][99][100][101] and femoral arteries 12) . The relative importance of NO to FMD may also be altered when conducting this test on patients with a number of diseased states, such as dystonia 26) , chronic heart failure 27) or hypertension 28) (see Table 2).…”
Section: Prostacyclinmentioning
confidence: 95%
See 1 more Smart Citation
“…PGI2 and Relative Contribution to Flow-Mediated Dilation Doshi et al 94) found that administration of NOS inhibitor N G -monomethyl-L-arginine (L-NMMA) completely abolished FMD of the brachial artery following 5 minutes of wrist cuff occlusion, with no difference in the hyperemic stimulus; however, L-NMMA does not completely block the FMD response when the occlusion cuff is placed on the upper arm 94,95) (see Table 1). Similarly, L-NMMA does not completely abolish FMD in the radial 11,27,28,[96][97][98][99][100][101] and femoral arteries 12) . The relative importance of NO to FMD may also be altered when conducting this test on patients with a number of diseased states, such as dystonia 26) , chronic heart failure 27) or hypertension 28) (see Table 2).…”
Section: Prostacyclinmentioning
confidence: 95%
“…Pyke et al 98) Fischer et al 99) Mullen et al 100) Pyke et al 98) Seddon et al 101) Mullen et al 100) Hornig et al…”
Section: )unclassified
“…2 In patients with angiographically normal coronary arteries, intracoronary infusion of the nNOS-selective inhibitor SMTC reduced basal coronary blood flow and epicardial coronary diameter but had no effect on increases in flow evoked by intracoronary substance P that stimulated the release of NO from the endothelium, whereas L-NMMA infusion reduced basal coronary flow and inhibited substance P-induced increases in flow. 65 Local nNOS-derived NO, possibly from nitrergic neurons innervating coronary arteries and arterioles (Fig. 1), appears to regulate basal coronary blood flow in humans.…”
Section: 23mentioning
confidence: 99%
“…The nNOS and eNOS have distinct local roles in the physiologic regulation of human coronary and peripheral microvascular tone in vivo. Whereas eNOS-generated NO facilitates dynamic alterations in blood flow distribution, the tonic generation of NO by nNOS may be important for the regulation of basal vasomotor tone and blood flow [25,26]. Hemoglobin, albumin, and glutathione carry and release nitric oxide (NO) within microvessels.…”
Section: Blood Flow Distributing Among Different Vascular Beds Are Rementioning
confidence: 99%
“…The nNOS and eNOS have distinct local roles in the physiologic regulation of human coronary and peripheral microvascular tone in vivo and then, that these isoforms may therefore subserve distinct functions. Whereas eNOS-generated NO facilitates dynamic alterations in blood flow distribution, the tonic generation of NO by nNOS may be important for the regulation of basal vasomotor tone and blood flow [25,26]. If Blood vessels are continuously subjected to mechanical forces in the form of stretching and this encompasses cyclic mechanical strain due to the pulsatile nature of blood flow and shear stress.…”
Section: Blood Flow Distribution Among Different Vascular Beds Is Regmentioning
confidence: 99%